2010
DOI: 10.1126/science.1195618
|View full text |Cite|
|
Sign up to set email alerts
|

Rewiring of Genetic Networks in Response to DNA Damage

Abstract: Although cellular behaviors are dynamic, the networks that govern these behaviors have been mapped primarily as static snapshots. Using an approach called differential epistasis mapping, we have discovered widespread changes in genetic interaction among yeast kinases, phosphatases, and transcription factors as the cell responds to DNA damage. Differential interactions uncover many gene functions that go undetected in static conditions. They are very effective at identifying DNA repair pathways, highlighting ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
440
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(472 citation statements)
references
References 26 publications
31
440
0
1
Order By: Relevance
“…47 An initial dNTP imbalance during the generation of shErk5 cells could later be compensated for by additional modifications to allow cell growth. Curiously, yeast Slt2, the functional homolog of human Erk5, is required for appropriate regulation of RNR genes in response to DNA damage, 48 and is necessary for resistance to dNTP deficiency induced by HU. 49,50 These data indicate different but related roles of Erk5 in mammals and yeast.…”
Section: Discussionmentioning
confidence: 99%
“…47 An initial dNTP imbalance during the generation of shErk5 cells could later be compensated for by additional modifications to allow cell growth. Curiously, yeast Slt2, the functional homolog of human Erk5, is required for appropriate regulation of RNR genes in response to DNA damage, 48 and is necessary for resistance to dNTP deficiency induced by HU. 49,50 These data indicate different but related roles of Erk5 in mammals and yeast.…”
Section: Discussionmentioning
confidence: 99%
“…One of the stronger counterexamples that can be cited is the observation that deletion of 12 of 31 tested genes in a high-scoring DNA damage cluster (cluster 4) did not cause increased GCR rates as single mutations. Sufficient genetic data exist for genes in cluster 4 to suggest that nonperturbed growth-based genetic interactions are only a crude surrogate for measuring similarity in suppressing GCRs, which is consistent with the substantial changes in synthetic lethal interactions between deletion mutations caused DNA damaging agents (31). Additionally, because only pair-wise interactions are typically identified, other kinds of important genetic results cannot be identified, such as suppression of the lethality of srs2Δ sgs1Δ double mutants by mutations causing homologous recombination defects (50), and because more complex genetic redundancies, which are particularly important in higher eukaryotes, cannot be handled.…”
Section: Discussionmentioning
confidence: 95%
“…However, the importance of these genes in the presence of DNA damaging agents is emphasized by the number of screens in which these genes were identified (Datasets S2 and S6) and is consistent with the known roles of these gene products. We note that the inability of unperturbed growth to capture the roles of these types of genes can be anticipated from decades of classic genetic studies as well as a recent report of changes in genetic interactions measured in a high-throughput manner due to the presence of MMS (31).…”
Section: Computational Analysis and Prioritization Of Candidate Genomementioning
confidence: 99%
“…MSN2 and YAP1 are both activators required for oxidative stress tolerance, and there is a partial overlap between their H 2 O 2 -inducible regulons (38). Studies using epistatic miniarray profiles (39,40) have shown that double mutations in MSN2 and YAP1 lead to severe fitness defect. Two more such examples can be found in SI Appendix, Fig.…”
Section: Real Data Examplesmentioning
confidence: 99%